OPTIMALISASI GAS METAN HASIL FERMENTASI METANOGENIK CAMPURAN KOTORAN TERNAK DENGAN LIMBAH KULIT PISANG (Musa spp) - , Abbas ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objectives of this research was to determine the influence of addition banana peel (Musa spp) into the manure, cow dung and horse dung as a substrates ot the fermentation process that includes content of volatile fatty acids (VFA) and methane production. Two treatment were conducted, P1 for biogas yield by cow dung substrate, and P2 for biogas yield by horse dung substrate. Each treatment performed in 3 levels and replicated 3 times, namely 100%:0%, 85%:15% and 70%:30%, with a sampling test every 10 th , 20 th , and 30 th days. Measured variable were the pH, temperature, volume of biogas, content of volatile acids and methane production. Substrate mixtures dissolved into water for each treatment were 1:2. Data processing using the split-plot design analysis, and then followed by Duncan Multiple Range Test (DMRT) to find out the average among the treatments for the observation of biogas volume measurement, and level of methane, sludge digester temperature, ambient temperature, and potential of Hydrogen (pH). Results showed that addition of banana peel influenced significantly (p<0,01) to protozoa colony, yield biogas, methane concentration and methane production (CH4), significant (p<0,05) to volatile fatty acids, but non significant to CMC-ase activity, temperature and pH of digester.